Diagnostic opportunities for evaluation of the exposure of dairy cows to the mycotoxins deoxynivalenol (DON) and zearalenone (ZEN): reliability of blood plasma, bile and follicular fluid as indicators. Issue 5 (31st December 2014) - Winkler, J.; Kersten, S.; Meyer, U.; Stinshoff, H.; Locher, L.; Rehage, J.; Wrenzycki, C.; Engelhardt, U. H.; Dänicke, S.
Summary: To investigate the usefulness of follicular fluid (FF) in relation to blood plasma and bile as indicators of exposure of dairy cows to ZEN, DON and their metabolites, a dose–response study was performed with 30 dairy cows. The cows, 10 in each group (named CON; FUS‐50, FUS‐100), received a diet with three different concentrations of Fusarium toxin‐contaminated maize. Thereby, the following dietary concentration were reached: CON (0.02 mg ZEN and 0.07 mg DON, per kg dry matter, DM), FUS‐50 (0.33 mg ZEN and 2.62 mg DON, per kg DM) and FUS‐100 (0.66 mg ZEN and 5.24 mg DON, per kg DM). ZEN, DON and de‐epoxy‐DON (de‐DON) were detected in FF. Based on the linear regression between toxin concentration in plasma and FF, it seems that about 50 % (m = 0.5) of ZEN present in plasma is present in FF while an increase of 1 ng/ml DON or de‐DON in plasma is paralleled by an increase of 1.5 ng/ml DON or 1.1 ng/ml de‐DON in FF. ZEN, DON and their metabolites, except zearalenone (ZAN), were also detected in bile. Contrary to DON and de‐DON, ZEN and its metabolites were accumulated in bile so that the concentration of ZEN and metabolites was much higher than for DON and de‐DON. The main compound was β ‐zearalenol ( β ‐ZEL). The biliary ZEN, α ‐zearalenol ( α ‐ZEL) and β ‐ZEL concentration correlated linearly with each other with an uncertainty of <15 % ( r 2  ≥ 0.86), whereas the ratio between ZEN: α ‐ZEL: β ‐ZEL was about 1.5:1:11. With the help of established linear relationship between toxin intake and toxin concentration, bile could be used as diagnostic indicator to assess the exposure of cows.